A study on clinical profile and outcome of patients in PICU (paediatric intensive care unit) at tertiary care unit - Jyothi K., Aruna; Ankireddy, Korisipati (International Journal of Contemporary Pediatrics, 2019)
Background: This study was carried out with the objectives to study the clinical profile and to find the outcome of children admitted to pediatric intensive care unit (PICU) of Kurnool medical college and hospital, Andhra Pradesh. Methods: A retrospective study was carried in children aged more than 28 days to 12 years admitted in PICU from 1st January 2016 to 31st December 2016 when a total of 600 patients were admitted. Results: Out of these, 400 (66.66%) cases were males and 200 (33.33%) cases were females. Maximum numbers of patients were in the age group of more than 28 days to 1 year which constituted 325 (54.16%) cases. This was followed by 1 year to less than 5 years age group which constituted 150 (i.e. 25%) cases. Under 5 years aged children constituted 500 (83.33%) cases. Next most common age group admitted was 5 years to 10 years with 85 (i.e. 14.16%) cases and 10 to 12 years age group constituted 40 (6.66%) cases. In this study, central nervous system was the commonest system involved (n=195, 32.5%). Other systems involved were: respiratory system (n=122, 20.33%), cardiovascular system (n=65, 10.83%), gastro-intestinal system (n=32, 5.33%), hematological (n=35, 5.83%) and renal system (n=23, 3.83%). Other causes include infections (n=97, 16.16%), metabolic (n=17, 2.83%), down syndrome (n=7, 1.16%) and poisoning (n=7, 1.16%) etc. Conclusions: Out of the 600 patients admitted to PICU, 168 (28%) patients died. 315 (52.5%) cases improved. 117 (19.5%) cases constituted those who were shifted to higher centre or another department or were taken against medical advice.